2023
DOI: 10.1590/ce.v28i0.89439
|View full text |Cite
|
Sign up to set email alerts
|

Telesimulación Como Método De Enseñanza a Distancia en Reanimación Cardiopulmonar: Informe De Experiencia

Abstract: RESUMEN Objetivo: describir la experiencia en la elaboración e implementación de un curso a distancia de Reanimación Cardiopulmonar para profesionales de la salud mediante Telesimulación. Desarrollo: informe de experiencia de un curso de capacitación en Reanimación Cardiopulmonar, realizado con 227 profesionales de la salud entre junio y julio de 2021, de forma remota y sincrónica, en el estado de Río de Janeiro, Brasil. Se dictó el curso a 35 grupos y se los sometió a: pretest; video clase y postest 1; y Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Like Smith and Hamilton [32], who support the use of VR simulation as a supplemental tool for teaching students, we consider that VR simulation is a BLS-AED teaching method with similar results compared to traditional face-to-face training. Regardless, Cerezo et al [27] found that the results are discreetly better. We believe, however, that it provides emotional, situational and reality qualities that no other methodology provides and should be introduced for future generations, in training aimed at teenagers and the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like Smith and Hamilton [32], who support the use of VR simulation as a supplemental tool for teaching students, we consider that VR simulation is a BLS-AED teaching method with similar results compared to traditional face-to-face training. Regardless, Cerezo et al [27] found that the results are discreetly better. We believe, however, that it provides emotional, situational and reality qualities that no other methodology provides and should be introduced for future generations, in training aimed at teenagers and the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Others interpret VR exclusively as online training [5] without comparison between groups. Regardless of the optimal duration, in our opinion, the most important thing is that the system manages to motivate the student, capture their attention and improve their learning [27].…”
Section: Discussionmentioning
confidence: 99%